Pengaruh Inflasi Dan Earning Per Share (EPS) Terhadap Harga Saham di Sektor Industri Barang Konsumsi pada Indeks Saham Syariah (ISSI) - Chairani Chairani; Gatot B Setiawan; Rachma Zannati (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2020)
Purpose-. The aim of this study is to examine the impact of inflation and earnings per share (EPS) on the share prices of the consumer goods sector. Methods- Data are collected from the financial statements in the Consumer Goods Industry Sector, namely 18 companies registered at ISSI. With the period 2014-2018 using a purposive sampling technique. Findings- The analysis results show that inflation has not been proven to have a significant effect on stock prices, while EPS has a positive and significant effect. The implication of this finding is that the fundamental factor information of EPS ratios in financial statements can be useful information to predict sharia stock prices